2017
DOI: 10.1002/chem.201703364
|View full text |Cite
|
Sign up to set email alerts
|

Heptazine: an Electron‐Deficient Fluorescent Core for Discotic Liquid Crystals

Abstract: Herein, room-temperature discotic liquid crystals based on heptazine, an electron deficient central core, are reported for the first time. Mesomorphic behaviors of the materials are also investigated. Supramolecular assembly of the mesophase derivatives were confirmed by X-ray scattering experiments. Heptazine-based solid thin films are strong blue light emitters, whereas in the solution state, they are weakly emissive or non-emissive. The band gap energy is found to be low in this class of compounds. Formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…In addition, many of the relatively rare heptazines known to date present desirable properties. Especially, their fluorescence emission 3 has been exploited in liquid crystalline materials 4 and OLEDs devices. 5 Finally, even more attracting, heptazine polymers have demonstrated outstanding photocatalytic properties, 6,7 and the heptazine core might well be one of the rare molecular platforms which could give birth to molecular catalysts able to perform water splitting [8][9][10] , the holy Grail of all photocatalytic processes.…”
Section: A Straightforward Synthesis Of a New Family Of Molecules: 2mentioning
confidence: 99%
“…In addition, many of the relatively rare heptazines known to date present desirable properties. Especially, their fluorescence emission 3 has been exploited in liquid crystalline materials 4 and OLEDs devices. 5 Finally, even more attracting, heptazine polymers have demonstrated outstanding photocatalytic properties, 6,7 and the heptazine core might well be one of the rare molecular platforms which could give birth to molecular catalysts able to perform water splitting [8][9][10] , the holy Grail of all photocatalytic processes.…”
Section: A Straightforward Synthesis Of a New Family Of Molecules: 2mentioning
confidence: 99%
“…Because of this reason, heptazines can be reversibly reduced at relatively high potentials,6 which makes them interesting compounds in view of applications for photovoltaic devices. They are also fluorescent,7 and heptazines displaying delayed fluorescence have been described 8,9. Most of them display a very high thermal stability,2 which is highly desirable for the development of light-emitting or photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%
“…However, a major drawback in heptazine synthetic chemistry lies in the fact that almost all derivatives that have already been reported are prepared starting from the only heptazine known to date to have exchangeable side groups, 2,5,8-trichloro-heptazine, (sometimes designated as cyameluric chloride). The Kroke group and other groups have indeed shown that the chlorides could be efficiently replaced by various nucleophiles, like amines,6,7 thiols,19 selenols19 and phosphines 20. This very useful synthon has, however, two major drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of the Hpz‐3C12 compound has been explained in the previous paper reported by our group . The Hpz‐3C12 molecule comprised the simplified structure (Figure ).…”
Section: Resultsmentioning
confidence: 99%